Formal String Instrument Training in a Class Setting Enhances Cognitive and Sensorimotor Development of Primary School Children - James, Clara E.; Zuber, Sascha; Dupuis-Lozeron, Elise; Abdili, Laura; Gervaise, Diane; Kliegel, Matthias (Frontiers in Neuroscience, 2020)
This cluster randomized controlled trial provides evidence that focused musical instrumental practice, in comparison to traditional sensitization to music, provokes multiple transfer effects in the cognitive and sensorimotor domain. Over the last two years of primary school (10-12 years old), 69 children received group music instruction by professional musicians twice a week as part of the regular school curriculum. The intervention group learned to play string instruments, whereas the control group (i.e. peers in parallel classes) was sensitized to music via listening, theory and some practice. Broad benefits manifested in the intervention group as compared to the control group for working memory, attention, processing speed, cognitive flexibility, matrix reasoning, sensorimotor hand function and bimanual coordination Apparently, learning to play a complex instrument in a dynamic group setting impacts development much stronger than classical sensitization to music. Our results therefore highlight the added value of intensive musical instrumental training in a group setting within the school curriculum, encouraging general implementation in public primary schools, thus better preparing children for secondary school and for daily living activities.